Are We Moving Too Fast?: Representation of Speed in Static Images - Irmak Hacımusaoğlu; Neil Cohn (Journal of Cognition)
Despite pictures being static representations, they use various cues to suggest dynamic motion. To investigate the effectiveness of different motion cues in conveying speed in static images, we conducted 3 experiments. In Experiment 1, we compared subjective speed ratings given for motion lines trailing behind movers, suppletion lines replacing parts of the movers and backfixing lines set in the background against the baseline of having no extra cue. Experiment 2 was a replication of the first experiment with an addition of several motion lines considering the effect of quantity on conveyed speed. Experiment 3 then examined the actual time assessments of each cue and bare objects indicated for movers to complete their paths. Our results showed that motion cues vary in their effectiveness in depicting speed, with some influence from proficiency in reading manga. Motion lines, which index the path being traversed, remained less effective than suppletion and backfixing lines, which we argue encode the speed component of motion rather than directionality. However, adding more motion lines intensified the perceived speed of the movers. These static cues also influenced the actual time durations individuals indicated for fictitious motion events, in line with the subjective speed ratings. Altogether, our results suggest that different aspects of motion can be captured by different cues, and that the effectiveness of cues might be modulated by exposure to such patterns, in line with the premises of a visual lexicon view.